TRAFFIC ARBITRATION - KALINICH, B.; KROTOV, A.; LYNNYK, S.; YELISYEYEVA, OXANA; BELOZERTSEV, VASYL (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In modern conditions, the rapid development of the global information society is being formed and taking place. The colossal level of development of network technologies allows users to earn money on the Internet in different ways. So today, earnings from traffic arbitrage is just one of the most profitable types on the Internet. You can make money on advertising on the Internet, if you can attract visitors to a particular site and consistently redirect them to another network portal. The work of an arbitrator is a daily hard work, you need to be constantly looking for new ideas, analyze successful cases and failures. The first large-scale example of the traffic business was the launch of an affiliate program by Amazon in July 1996. At that time, it was not the first, but certainly the most popular on the Internet. For a long time, this program was considered one of the most convenient "entry points" in the field for beginners. But in April 2020, Amazon reduced its commission payments immediately by 80%, making it much less attractive to webmasters. Today, traffic arbitrage is a very promising area in terms of earnings. This is a risky business, because without a competent approach to the case, without analyzing the market situation and without observing the statistics, you can lose a lot of time and money. Buying traffic is already an expense, and whether there will be income and what size is unknown. Even experienced professionals do not immediately make a profit. The article highlights the specifics of traffic arbitrage, webmaster work, CPA network. The essence of the arbitrator’s work, methods of profit and basic principles of work are revealed. The pros and cons, advantages and risks of arbitration in the field of digital marketing are considered. The main steps from which to start a robot in the traffic business are highlighted step by step. Features of work of the arbitrator and CPA-networks are revealed. The answers of the work for the last years according to the scientometric databases Google Scholar and ResearchGate are analyzed. It is determined that traffic arbitrage is a unique and risky field that requires technical skills and analytical skills from specialists. The main components for successful work with traffic are generalized. Various sources of income and the main search engines from traffic arbitrage are described. Traffic sources are analyzed. the corresponding conclusions are made. Insufficient number of scientific works on current trends in traffic arbitrage has been proved.